Problematika Pelaksanaan Program Pendaftaran Tanah Sistematis Lengkap (PTSL) Terhadap Pendaftaran Tanah Yang Berkepastian Hukum - Permadi, Iwan (JUSTISI, 2024)
The Complete Systematic Land Registration Program (PTSL) responds to the public’s grievances about complex land registration services, requiring no small cost and a long process. PTSL organizes land registration simultaneously, inexpensively, openly and quickly, but in its implementation provides opportunities for the existence of authority abuse and misconduct. This study examines the problem of complete systematic land registration versus legal uncertainty land registrations. The method of research used is the normative jurisprudence with the method of approaching legislative regulations and conceptual approaches. The results of the research show that the maintenance of a complete systematic land registration program can reduce the legal certainty and protection of its owners, due to corrupt acts, wild charges and misrepresentation in its implementation. Coordination with relevant parties between BPN, local governments, police and the public is necessary to minimize the occurrence of confusion and abuse of authority.